The influences of CD4 cell count, viral load and antiretroviral treatment on left ventricle ejection fraction of adult HIV/AIDS patients - Steenkamp, Sonja (Bloemfontein: Central University of Technology, Free State, 2004)
This research project compared the influence of the CD4 cell count, the viral load and antiretroviral therapy (ARn on the left ventricle ejection fraction (LVEF). The purpose was to see what the relationship between the variables was in an attempt to find a point in the course of the HIV/AIDS disease where it is necessary to do an echocardiogram on these patients to evaluate the LVEF. All the data of the variables were included against the inclusion and exclusion criteria. An echocardiogram was done on all those HIV/AIDS diagnosed patients who gave their consent to evaluate the LVEF. The patients then went for their usual blood tests and ART was given if it was indicated. The findings show that there was a direct proportional relationship between the LVEF and the CD4 cell count, and an indirect proportional relationship between the viral load and the LVEF. The prevalence of a below normal LVEF was mostly found in patients whose CD4 cell count was below or equal to 100 cells/ml and/or the viral load above or equal to 100 000 RNA copies/ml. The majority of patients whose LVEF was below normal and whose viral load was equal to or below 100 000 RNA copies/ml were on antiretroviral therapy. When the viral load exceeded the cut-off point of 100 000 RNA copies/ml, the patients who were not on ART with a below normal LVEF exceeded those who were on ART. The majority of patients with a low CD4 cell count whose LVEF was below normal were not on antiretroviral therapy. It was also found that the ART had a direct positive effect on the CD4 cell count and the viral load, and indirectly on the LVEF. Therefore, because of the relationship between the CD4 cell count and the LVEF and the viral load and the LVEF, ART had an indirect effect on the LVEF via the CD4 cell count and/or the viral load. This means that if there was an increase in the CD4 cell count due to the ART, then one could expect to see a rise in the LVEF because of the direct proportional relationship between the CD4 cell count and the LVEF. If the ART led to a decrease in the viral load, then one could expect that the LVEF would increase due to an indirect proportional relationship between the viral load and the LVEF. Successful antiretroviral therapy had a positive effect on the CD4 cell count and the viral load, and an indirect positive effect on the LVEF (via the CD4 cell count and/or the viral load). To conclude, the treating physician of ~n adult HIV/AIDS patient should consider an echocardiogram on all these patients when the CD4 cell count falls below 100 copies/ml, and/or when the viral load exceeds 100 000 RNA copies/ml in order to identify those patients who have left ventricular dysfunction and who might therefore benefit from treatment with appropriate medication.
Thesis
Keywords: Antiretroviral agents - South Africa; HIV (Viruses) - Treatment - South Africa; Aids (Disease) - Patients; Heart - Diseases - Immunological aspects